A shift toward personalized healthcare: does the Affordable Care Act provide enough incentive for change?. (June 2015) - Teng, Kathryn
Personalized healthcare, which uses individual characteristics to better predict and prevent disease and customize therapies, is a potential solution to our current healthcare crisis. Personalized care aims to improve quality of care and reduce overall healthcare costs. Despite its potential, adoption of personalized healthcare has been slow for several reasons, one of which is related to financial incentives toward change. This perspective piece discusses how the Affordable Care Act (ACA), through support for preventive care and comparative effectiveness research, begins to align the right incentives toward innovation around personalized risk prediction, innovation that is much needed as we aim to improve the health of individuals and communities.